Pengembangan SDM Pokdarwis Desa Wisata Sungai Awan Kiri melalui Clean, Health, Safety, and Environmental Sustainbility (CHSE) - Betti Ses Eka Polonia; Ahmad Ravi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Ministry of Tourism and Creative Economy again held a Tourism Village Community Empowerment Program. The collaboration between the Ministry of Tourism and Creative Economy, the Ministry of Villages for Disadvantaged Regions, and Transmigration and Higher Education is one of its forms. Higher education institutions are required to carry out community service programs. One of these activities is in the form of human resource development activities involved in the management of tourism villages, namely Pokdarwis (Tourism Awareness Group). One of the human resource developments carried out is the strengthening of CHSE (Clean, Health, Safety, and Environmental Sustainability) materials. CHSE is a new program that is being socialized by the Ministry of Tourism and Creative Economy to encourage healthy and safe tourism activities in all tourism destinations. Also, with the existence of correct and adequate CHSE and health protocols, it becomes one of the attractions for tourists to visit tourist villages. This activity was attended by 25 participants from Pokdarwis (Tourism Awareness Group), Sungai Awan Kiri Tourism Village, Ketapang, West Kalimantan. This activity aims to improve the competence of human resources for managing the Sungai Awan Kiri Tourism Village which is closely related to CHSE, K3, and the implementation of health protocols that must be implemented in the New Normal era in tourist villages.